EFEKTIFITAS TERAPI MUSIK CAMPURSARI TERHADAP RESIKO PERILAKU KEKERASAN PADA PASIEN SKIZOFRENIA DI RSJ. DR. RADJIMAN WEDIODININGRAT LAWANG - Ike Prafita Sari; Hendro Subagio; Mujiadi (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Violent behavior in schizophrenia sufferers can occur towards other people and themselves and they are unable to respond to the environment. Where the patient experiences panic and his behavior is controlled by his anger. Patients can commit suicide (suicide), kill other people (homicide) and damage the environment. One solution is providing Campursari music therapy. The aim of the research was to determine the effect of Campursari music therapy on the risk of violent behavior in schizophrenia patients in the Bangau Room at RSJ Dr. Radjiman Wediodiningrat Lawang. The research method uses a pre-experimental research design with a pre-test and post-test design in one group (One Group Pre-post test Design). The sampling technique used Simple Random Sampling with a total of 19 respondents. Data collection was carried out in May - June 2023. The pre-test results obtained mostly had a risk of violent behavior in the medium category, namely 12 people (63.2%), while the post-test results were obtained partially. 17 people (89.5%) had a large risk of violent behavior in the Low category. The results of the Wilcoxon test obtained a value of Z = -3.725 with a significance of 0.000 (p<0.05), meaning that Campursari Music Therapy is effective against the risk of violent behavior in schizophrenia patients at RSJ Dr.Radjiman Wediodiningrat Lawang. Campursari music therapy can reduce the risk of violent behavior in treating schizophrenia patients, so this could be an alternative therapy to prevent violent behavior. Keywords: Campursari Music Therapy, Risk of Violent Behavior, Schizophrenia